Individual tree context and contrast dictate tree physiological features and arthropod biodiversity patterns across multiple trophic levels. (22nd October 2019) - Swart, Rudi C.; Samways, Michael J.; Pryke, James S.; Roets, Francois
Abstract : 1. The present study tested the hypothesis that tree context (natural, semi‐natural or planted) and contrast (height of surrounding vegetation) affect tree physiological characters (leaf size, nutrient content, and stress‐related factors), and also alter the arthropod biodiversity patterns either directly or indirectly. 2. Arthropods were collected from tree canopies using chemical fogging from the ecologically important South African native tree Podocarpus elongatus . 3. Low contrast trees had significantly larger leaves than those in high contrast environments and harboured an overall higher richness, abundance, and biomass of arthropods, although this was guild‐dependent. 4. Trees in natural contexts had less foliar δ 13 C, suffered less from artificial nitrogen enrichment, and harboured significantly higher herbivore and predator arthropod richness and unique assemblages, compared with planted trees. 5. Semi‐natural trees supported natural levels of arthropod richness, although these were mostly generalist species. 6. Tree context and contrast can therefore dictate associated biota at multiple trophic levels and native trees may fail to maintain natural biodiversity in transformed landscapes. Abstract : Low contrast trees had significantly larger leaves than those in high contrast environments and harboured an overall higher richness, abundance, and biomass of arthropods, although this was guild‐dependent. Trees in natural contexts had less foliar δ 13 C, suffered less from artificial nitrogen enrichment, and harboured higher herbivore and predator arthropod richness and unique assemblages, compared with planted trees. Tree context and contrast can therefore dictate associated biota at multiple trophic levels and native trees may fail to maintain natural biodiversity in transformed landscapes.